Effect of early prophylactic low-dose recombinant human erythropoietin on retinopathy of prematurity in very preterm infants - Sun, Huiqing (J Transl Med, 2020)
BACKGROUND: Very preterm infants are at risk of developing retinopathy of prematurity (ROP). Recombinant human erythropoietin (rhEPO) is routinely used to prevent anemia in preterm infants; however, the effect of rhEPO on ROP development is still controversial. The purpose of this study was to evaluate the effect of early prophylactic low-dose rhEPO administration on ROP development in very preterm infants. METHODS: A total of 1898 preterm infants born before 32 weeks of gestation were included. Preterm infants received rhEPO (n = 950; 500 U/kg, rhEPO group) or saline (n = 948, control group) intravenously within 72 h of birth and then once every other day for 2 weeks. RESULTS: The total incidence of ROP was not significantly different between the two groups (10.2% vs. 13.2%, p = 0.055). Further analysis showed that rhEPO group had lower rates of type 2 ROP than the control group (2.2% vs. 4.1%, RR 0.98; 95% CI 0.96–1.00; p = 0.021). Subgroup analysis found that rhEPO treatment significantly decreased the incidence of type 2 ROP in infant boys (1.8% vs. 4.3%, p = 0.021) and in those with a gestational age of 28–29(6/7) weeks (1.1% vs. 4.9%, p = 0.002) and birth weight of 1000–1499 g (1.2% vs. 4.2%, p = 0.002). There was a small increasing tendency for the incidence of ROP in infants with a gestational age of < 28 weeks after rhEPO treatment. CONCLUSIONS: Repeated low-dose rhEPO administration has no significant influence on the development of ROP; however, it may be effective for type 2 ROP in infant boys or in infants with gestational age > 28 weeks and birth weight > 1500 g. Trial registration The data of this study were retrieved from two clinical studies registered ClinicalTrials.gov (NCT 02036073) on January 14, 2014, https://clinicaltrials.gov/ct2/show/NCT02036073; and (NCT03919500) on April 18, 2019. https://clinicaltrials.gov/ct2/show/NCT03919500.